A data-driven framework for effective single-group cross section adjustment in point-depletion burnup calculations - Wei-Jia Meng; Te Sheng; Ou-Yi Li; Gang-Lin Yu (Annals of Nuclear Energy, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Synthesis and production of hydroxytyrosol derivatives with potent anti-inflammatory activities - Te-Sheng Chang; Wen-Yueh Ho; Jiumn-Yih Wu; Chien-Yu Wu; Pei-Rong Cai; Bo Eng Cheong; Wilson Thau Lym Yong; Peik Lin Teoh (Natural Product Research, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Synergistic enhancement of PBAT biodegradation by Purpureocillium lilacinum BA1S: Insights from transcriptomics and functional analyses - Wei-Sung Tseng; Min-Jia Lee; Tzu-Yen Chen; Shih-Shun Lin; Sheng-Lung Chang; Pei-Yin Lin; Ting-Jang Lu; Chi-Te Liu (Journal of Hazardous Materials, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Validation of the constitution in Chinese medicine questionnaires with the newly developed blood-vacuity category: a rare Taiwanese case study - Ting-Yu Huang; Shi-Chen Ou; Wei-Te Huang; Yu-Chuan Lin; Hao-Hsiu Hung; Chin-Wei Chang; Kai-Yuan Hsiao; Yi-Wei Kao; Chien-Hua Wu; Wei-Shan Chang; Ben-Chang Shia; Sheng-Teng Huang (Advances in Traditional Medicine, 2024)

ClinOleic Impairs ROS Production and Phagocytosis in M1 Macrophages Without Affecting M1 Differentiation - Yi-Sheng Tsai; Hsuan-Te Yeh; Ming-Shan Chen; Hui-Ju Chang; Wen-Chun Lin; Shew-Meei Sheu (Cell Biochemistry and Biophysics, 2024)

Columnar aerosol types and compositions over peninsular Southeast Asia based on long-term AERONET data - Sheng-Hsiang Wang; Hsiang-Yu Huang; Che-Hsuan Lin; Shantanu Kumar Pani; Neng-Huei Lin; Chung-Te Lee; Serm Janjai; Brent N. Holben; Somporn Chantara (Air Quality, Atmosphere & Health, 2024)
Aerosol chemical components such as black carbon (BC) and brown carbon (BrC) regulate aerosol optical properties, which in turn drive the atmospheric radiative forcing estimations due to aerosols. In this study, we used the long-term measurements from AERONET (Aerosol Robotic Network) to better understand the aerosol types and composition with respect to their seasonal and spatial variabilities in peninsular Southeast Asia (PSEA, here defined as Vietnam, Cambodia, Thailand, Laos, and Myanmar). Two methods (i.e., aerosol type cluster and aerosol component retrieval) were applied to determine the aerosol type and chemical composition during the biomass-burning (BB) season. AERONET sites in northern PSEA showed a higher AOD (aerosol optical depth) compared to that of southern PSEA. Differences in land use pattern, geographic location, and weather regime caused much of the aerosol variability over PSEA. Lower single-scattering albedo (SSA) and higher fine-mode fraction (FMF) values were observed in February and March, suggesting the predominance of BB type aerosols with finer and stronger absorbing particles during the dry season. However, we also found that the peak BB month (i.e., March) in northern PSEA may not coincide with the lowest SSA once dust particles have mixed with the other aerosols. Furthermore, we investigated two severe BB events in March of 2014 and 2015, revealing a significant BrC fraction during BB event days. On high AOD days, although the BC fraction was high, the BrC fraction remained low due to lack of aerosol aging. This study highlights the dominance of carbonaceous aerosols in the PSEA atmosphere during the BB season, while also revealing that transported dust particles and BrC aerosol aging may introduce uncertainties into the aerosol radiative forcing calculation.

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Analysis and classification of coffee beans using single coffee bean mass spectrometry with machine learning strategy - Jia-Jen Tsai; Che-Chia Chang; De-Yi Huang; Te-Sheng Lin; Yu-Chie Chen (Food Chemistry, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Edge-based wireless imaging system for continuous monitoring of insect pests in a remote outdoor mango orchard - Dan Jeric Arcega Rustia; Wei-Che Lee; Chen-Yi Lu; Ya-Fang Wu; Pei-Yu Shih; Sheng-Kuan Chen; Jui-Yung Chung; Ta-Te Lin (Computers and Electronics in Agriculture, 2023)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Toward a higher yield: a wireless sensor network-based temperature monitoring and fan-circulating system for precision cultivation in plant factories - Joe-Air Jiang; Min-Sheng Liao; Tzu-Shiang Lin; Chen-Kang Huang; Cheng-Ying Chou; Shih-Hao Yeh; Ta-Te Lin; Wei Fang (Precision Agriculture, 2018)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.